A Peran Guru dalam Mengembangkan Partispasi Anak Berkebutuhan Khusus Autis di Sekolah Inklusi - Azzahra, Aulia; Adha, Annisa; Nur Aini, Kharisma Risa; Minsih, Minsih (JPI (Jurnal Pendidikan Inklusi), 2023)
Inclusive education is a new perception in the field of education in Indonesia in providing educational services for all students, including children with special needs. Several elementary schools already have educational equality for children with special needs to place them with regular children who are accompanied by special assistant teachers. The purpose of the study was to explain the role of teachers as an effort to develop the participation of children with special needs, especially autistic children in the learning process in regular classes. Qualitative methods were used with a case study design, which aims to understand social phenomena descriptively. Data collection was carried out by direct observation of learning and interviews with homeroom teachers and special assistant teachers for autistic children. The results of the study explained that every child with special needs in a regular class is supervised by a designated assistant teacher. In the context of inclusive schools, assistant teachers play a role in adjusting lessons in class according to the needs of inclusive children, as well as providing assessments based on the child's abilities. Other efforts made include holding competitions with children with special needs as participants, to increase their participation. Therefore, support from the government, educational institutions, and the wider community is needed to achieve the goals of inclusive education.Keywords: Autistic Children, Student Participation, Learning